Пленница: [роман] / Татьяна Устинова, Павел Астахов - Устинова Татьяна Витальевна (Дела судебные, 2023)
Экземпляры: ф.12 (20240515) / Инвентарный номер: 64668 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: У 80 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.7